If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1 = 2x + -3 Reorder the terms: -1 + 7x = 2x + -3 Reorder the terms: -1 + 7x = -3 + 2x Solving -1 + 7x = -3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -1 + 7x + -2x = -3 + 2x + -2x Combine like terms: 7x + -2x = 5x -1 + 5x = -3 + 2x + -2x Combine like terms: 2x + -2x = 0 -1 + 5x = -3 + 0 -1 + 5x = -3 Add '1' to each side of the equation. -1 + 1 + 5x = -3 + 1 Combine like terms: -1 + 1 = 0 0 + 5x = -3 + 1 5x = -3 + 1 Combine like terms: -3 + 1 = -2 5x = -2 Divide each side by '5'. x = -0.4 Simplifying x = -0.4
| 5-3x=3x-25 | | 527=31n | | 2x-3=6+2x | | -80.2-9x=1.7 | | 10x-75=51+4x | | o=5-(2x-17) | | x+3.07+2.5=1.8 | | -80.2-9x=-21.9 | | 10a+55b= | | 3x+7-9x=-11 | | x+43=87 | | x+5=1.5x+2.5 | | 10f+2(5f+8)=-10f-4(2f-30) | | 5d+9=24 | | 2=17 | | 8ex=7 | | p*(q+r)=qp+pr | | y^2+9xy+18x^2=0 | | 32860-0.06x=x | | 7y+5=6y | | -43+11x=6x+32 | | -2k-16=3h-6 | | 2(x+4)=12x+62 | | 46=-6-8 | | 269.50=14 | | X-.4x=60 | | 20x+10y=0 | | 19-11n+16n-4= | | 9u^2+1u-10=0 | | X-x(.4)=60 | | 20x+10y=107 | | 3x+10=6x-19 |